2008
DOI: 10.1159/000170910
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Status over Two Years in Patients with Multiple Sclerosis

Abstract: Background: Smoking increases the risk of multiple sclerosis (MS) and possibly disease progression. The reliability of self-reported smoking status is unknown in MS. We assessed the reliability of self-reported smoking status among participants in the North American Research Committee on Multiple Sclerosis (NARCOMS) Registry. Methods: In 2004 and 2006, NARCOMS participants reported smoking status using Behavioral Risk Factor Surveillance Survey questions. We compared responses from 5,458 participants answering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
0
13
0
1
Order By: Relevance
“…ulcerative colitis; Boyko et al , 1987). The evaluation of the magnitude of the effect of cigarette smoking on the clinical course of multiple sclerosis may help to determine underlying disease mechanisms and is important, as studies have reported a high percentage of smokers amongst patients with multiple sclerosis (Marrie et al , 2009). Here we examine the effects of smoking on the disability progression and explore the potential benefit of smoking cessation using data from a well-documented, substantial, clinical cohort of patients with multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…ulcerative colitis; Boyko et al , 1987). The evaluation of the magnitude of the effect of cigarette smoking on the clinical course of multiple sclerosis may help to determine underlying disease mechanisms and is important, as studies have reported a high percentage of smokers amongst patients with multiple sclerosis (Marrie et al , 2009). Here we examine the effects of smoking on the disability progression and explore the potential benefit of smoking cessation using data from a well-documented, substantial, clinical cohort of patients with multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Th ere is strong evidence from meta-analysis and case-control studies that smoking is associated with MS [12][13][14][15][16] . Although self-reported smoking status can be reliable, the accuracy of this measure is reduced in lower socioeconomic groups, younger ages, and in some ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Th e main source of case identifi cation were hospital medical fi les, with relevant medical data routinely collected by neurologists at the Neuroimmunology and Neurogenetics Unit, Clinical Department of Neurology, Sestre milosrdnice University Hospital Centre in Zagreb, Croatia, during hospitalization. Relevant registry data included the following: age and gender; family history of MS; data on previous immunization: vaccination for morbillivirus (measles virus), parotitis virus (mumps) and rubella virus, hepatitis B virus (HBV), and other nonspecifi c vaccination; MS disease course (primary progressive MS (PPMS), remitting relapsing MS (RRMS), or secondary progressive MS (SPMS); Expanded Disability Status Scale (EDSS) score; cerebral magnetic resonance imaging (MRI) T2/FLAIR lesion load quantifi cation: moderate lesion load (0-9), signifi cant lesion load (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and progressive lesion load (more than 20); cerebrospinal fl uid (CSF) examination: protein index for evaluation of intrathecal IgG synthesis, evaluation of the blood-brain-barrier permeability, presence of oligoclonal bands (OCBs); evaluation of polyspecifi c, intrathecal humoral immune response against viral agents including antibodies to measles, rubella and varicella zoster virus (MRZ) reaction (MRZR); and further CSF analysis for Borrelia burgdorferi, neurotropic viruses, and central nervous system (CNS) parasites. Lifestyle habits, smoking and alcohol consumption were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Study strengths include the use of a large, well-characterized cohort of MS patients with a range of sociodemographic characteristics, experienced at completing questionnaires. We have shown previously that this cohort reports smoking status consistently over time, with a = 0.90 (95% CI: 0.89-0.92) for ever-smoking, and a = 0.92 (95% CI: 0.90-0.94) for current smoking [21] , and the questions we used have been widely used in national studies in the USA [9] . Results were consistent in the two analyses and robust to sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%